1995
DOI: 10.1002/jcb.240590816
|View full text |Cite
|
Sign up to set email alerts
|

Development of difluoromethylornithine as a chemoprevention agent for the management of colon cancer

Abstract: D,L-␣-difluoromethylornithine (DFMO) was synthesized over 20 years ago. It was hoped that this enzymeactivated, irreversible inhibitor of ornithine decarboxylase, the first enzyme in polyamine synthesis, would be effective as a chemotherapy for hyperproliferative diseases, including cancer and/or infectious processes. DFMO was generally found to exert cytostatic effects on mammalian cells and tissues, and its effectiveness as a therapeutic agent has been modest. DFMO was also found to cause treatment-limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
248
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(259 citation statements)
references
References 37 publications
11
248
0
Order By: Relevance
“…DFMO inhibits intestinal polyp formation in Apc Min/+ mice 32 . APC mutations are found in almost all sporadic (nonhereditary) forms of colon cancer, and ODC levels are increased in colon polyps in humans 18 . Our group has therefore carried out chemoprevention trials with DFMO in patients with FAP and sporadic colon polyps.…”
Section: Box 2 | Mechanisms Of Polyamine-dependent Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…DFMO inhibits intestinal polyp formation in Apc Min/+ mice 32 . APC mutations are found in almost all sporadic (nonhereditary) forms of colon cancer, and ODC levels are increased in colon polyps in humans 18 . Our group has therefore carried out chemoprevention trials with DFMO in patients with FAP and sporadic colon polyps.…”
Section: Box 2 | Mechanisms Of Polyamine-dependent Gene Expressionmentioning
confidence: 99%
“…The mechanism of this effect is thought to involve inhibition of the increased cell proliferation that is associated with the promotion phase. Subsequent studies indicated that DFMO was a potent inhibitor of epithelial carcinogenesis in a range of models, including those for skin, breast and colon 18 . …”
Section: Use Of Dfmo For Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 80% of liver cancer patients are diagnosed with hepatocellular carcinoma, which is resistant to most conventional chemotherapeutic agents (Wilson et al, 2012). Moreover, the use of chemoprevention agents is typically associated with side effects that lead to the destruction of normal tissues, such as those of the digestive, hematopoietic and nervous systems (Meyskens and Gerner, 1999;Suzuki et al, 2008;Florea and Büsselberg, 2011). The development of drugs that specifically target tumor cells, but not normal cells, represents a common goal.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, patients with BE and mucosal dysplasia are prime candidates for secondary prevention approaches, including chemoprevention, given their increased risk for developing esophageal adenocarcinoma. Difluoromethylornithine (DMFO) is a chemopreventive agent that irreversibly inhibits ornithine decarboxylase (ODC) that has been shown to decrease tissue polyamine levels and tumorigenesis (5,6). Polyamines are produced during cellular metabolism and act as signaling molecules for cell growth and differentiation (5).…”
Section: Introductionmentioning
confidence: 99%